POLA INTERAKSI SOSIAL ETNIS BUGIS DENGAN MADURA DI PUNGGUR KECIL KABUPATEN KUBU RAYA - Ardiansyah, Mukhlis Novi; Imran, Imran; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the Pattern of Bugis Ethnic Social Interaction with Madurese in Punggur Kecil Kubu Raya Regency. The form used in this research is qualitative with descriptive methods. Data collection techniques used were observation, interview, and documentation study, while the data collection tools were observation guides, interview guides, and documentation. The results of the study showed that spontaneous cooperation, namely cooperation carried out without orders from anyone, was shown by helping one another when there were residents who experienced the disaster. Individual competition in inter-ethnic trade, group competition in each ethnic group, for example soccer matches. Accommodation, that is, tolerance, that expresses opinions when musyaarawah among citizens, they are not individualistic or alone, but waiting for each other to avoid disputes, compromise is obtained both in small gatherings such as marriages or other parties, has become a tradition.Keywords: Ethnic Bugis with Madura Social Interactio, and Pattern.